2001
DOI: 10.1080/09629350120080401
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyleneiodonium inhibits NF‐κB activation and iNOS expression induced by IL‐1β: involvement of reactive oxygen species

Abstract: AIMS: In this work, we studied the mechanisms by which diphenyleneiodonium chloride (DPI) inhibits nitric oxide (NO) synthesis induced by the proinflammatory cytokine interleukin-1beta (IL-1) in bovine articular chondrocytes. To achieve this, we evaluated the ability of DPI to inhibit the expression and activity of the inducible isoform of the NO synthase (iNOS) induced by IL-1. We also studied the ability of DPI to prevent IL-1-induced NF-kappaB activation and reactive oxygen species (ROS) production. RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 43 publications
(27 reference statements)
5
38
0
Order By: Relevance
“…The activation of p38 MAP kinase and NF-κB nuclear translocation by HA oligos are in common with the stimulation of NO due to treatment of cells with IL-1 (Badger et al, 1998;Clancy et al, 2004;Mendes et al, 2001). In this study we demonstrated that this similarity was not due to HA oligos -induced autocrine release of endogenous IL-1 (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The activation of p38 MAP kinase and NF-κB nuclear translocation by HA oligos are in common with the stimulation of NO due to treatment of cells with IL-1 (Badger et al, 1998;Clancy et al, 2004;Mendes et al, 2001). In this study we demonstrated that this similarity was not due to HA oligos -induced autocrine release of endogenous IL-1 (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…To further explore the role of the iNOS in the NO signaling pathway, bovine chondrocytes in alginate beads were stimulated with IL-1α or HA oligos in the presence or absence of DPI, a flavin-dependent inhibitor of iNOS enzymatic activity (Mendes, Carvalho, Caramona, & Lopes, 2001). As shown in Fig.…”
Section: Induction Of Inosmentioning
confidence: 99%
“…EGF, a known stimulant of Nox1, was found to induce chemiluminescence in BeWo cells and its effect was inhibited by DPI. Although DPI was found to inhibit all FAD-binding enzymes, including nitric oxide synthase [38] and P450 enzymes [39] at higher concentrations, a relatively lower concentration (e.g., 30 μM, not shown) needed for EGF-induced activation suggests that an NADPH oxidase was involved. Previous studies employing Western blot analysis has shown multiple bands of Nox1 in vascular smooth muscle cells [40] and in Cos-7 cells transfected with Nox1 expression plasmid [41].…”
Section: Discussionmentioning
confidence: 99%
“…Spermine, an end-product of polyamine biosynthesis from L-arginine, is a competitive inhibitor of n-and i-NOS [23][24][25]. DPI is an i-NOS inhibitor [26,27]. All drugs were prepared as stock solutions in distilled water.…”
Section: Methodsmentioning
confidence: 99%